Toll-Like Receptors as Novel Therapeutic Targets for Ovarian Cancer. (4th March 2012) - Muccioli, Maria; Sprague, Leslee; Nandigam, Harika; Pate, Michelle; Benencia, Fabian
Abstract : Ovarian cancer (OC) is an aggressive disease that affects approximately 1 in 70 women and has a poor prognosis (<50%, 5-year survival rate), in part because it is often diagnosed at a late stage. There are three main types of OC: neoplasms of surface epithelial, germ cell, or stromal origin, with surface epithelial tumors comprising about 80% of all OCs. In addition to improving diagnostics, it is necessary to develop more effective treatments for epithelial-origin OC. Here, we describe the paradoxical roles of toll-like receptor (TLR) signaling in the progression of cancer and discuss how its modulation may result in decreased tumor growth and metastasis via the attenuation of proangiogenic cytokines and potentiation of proapoptotic factors. In particular, it has been found that TLR activity can behave like a "double-edged sword", as its signaling pathways have been implicated as having both tumor-suppressive and tumor-promoting effects. With particular emphasis on OC, we discuss the need to consider the signaling details of TLRs and associated proteins in the multiple cell types present in the tumor milieu to achieve safe and effective design of TLR-based cancer therapies.